Risk Identification of Severe Flood and Drought in Minjiang River Basin - WU Jing (Renmin Zhujiang)
To improve the scheduling plan for extreme hydrological events and severe drought and flood risks in the Minjiang River Basin, this paper employs the standardized runoff index SRI and standardized precipitation index SPI to identify and analyze the severe flood and drought risks in Minjiang River Basin according to the historical observation data of the basin.The results are as follows.①First, according to the drought and flood analysis on the time scale of year, there are four typical years in total including the typical drought years of 2003 and 2004 and the typical flood years of 1998 and 2016.The flood occurrence frequency is relatively low in the areas with high drought frequency in the Minjiang River Basin.②Second, according to the seasonal time scale analysis of drought and flood, the risk years of severe drought and flood in Minjiang River Basin in four seasons can be obtained, in which the spring and summer are dominated by extreme drought, and the autumn and winter are dominated by extreme flood.Meanwhile, the Z value of the four seasons SPI3 in Minjiang River Basin has a certain changing trend except in spring.In summary, the research results can provide basic data and technical support for coping with extreme hydrological events of drought and flood in the Minjiang River Basin in the future, and formulating emergency dispatching plans for severe drought and flood risks.